Odpowiedzi

2010-03-21T09:12:11+01:00
A) (-4xyz)*(- 1/2x²yz)= 2x³y²z²
b) (24a³b³c²):(8ab²c)= 3a²bc
c)(2/3x³y)/(1/3x³y)= 2
Najlepsza Odpowiedź!
2010-03-21T09:21:51+01:00

a) (- 4xyz) * ( - 1/2x"yz) =
(-4xyz)*(-1/2x²yz) = 4/2x³y²z² = 2x³y²z²

b) (24a"'b"'c"):( 8ab"c)=
(24a³b³c²)/(8ab²c) = 3a²bc

c) 2/3x"'y"
--------- =
1/3x"'y

(2/3x³y²)/(1/3x³y) = 2x⁰y=2y
  • g36k
  • Rozwiązujący
2010-03-21T09:28:15+01:00
W pierwszym wyszło mi -10x'''y''z''
drugim 3a''bc
trzecim 2,5xy
nie wiem czy dobrze, ale raczej tak : )